已知函数 $f(x)=\mathrm{e}^x-x+\mathrm{e}^3 a$, 其中 $-\frac{6}{5} \leqslant a < \frac{3}{\mathrm{e}^3}-1$, 函数 $f(x)$ 在 $(0,+\infty)$ 上的零点为 $x_0$, 函数 $g(x)=\left\{\begin{array}{l}x+a-\frac{x-a}{\mathrm{e}^x}, 0 \leqslant x \leqslant x_0, \\ (1-x) \ln x-a(x+1), x > x_0 .\end{array}\right.$
(1)证明:
(1) $3 < x_0 < 4$;
(2) 函数 $g(x)$ 有两个零点;
(2) 设 $g(x)$ 的两个零点为 $x_1, x_2\left(x_1 < x_2\right)$, 证明: $\frac{\mathrm{e}^{x_2}-x_2}{\mathrm{e}^{x_1}-x_1} > \mathrm{e}^{\frac{x_1+x_2}{2}}$.
(参考数据: $\mathrm{e} \approx 2.72, \mathrm{e}^2 \approx 7.39, \mathrm{e}^3 \approx 20.09, \ln 2 \approx 0.69, \ln 3 \approx 1.1$ )
【答案】 【解析】(1) (1) $\because f^{\prime}(x)=\mathrm{e}^x-1$, 当 $x > 0$ 时, $\mathrm{e}^x$
$ > 1$,
$\therefore f^{\prime}(x) > 0, \therefore f(x)$ 在 $(0,+\infty)$ 单调递增,
$$
\begin{aligned}
& \because-\frac{6}{5} \leqslant a < \frac{3}{\mathrm{e}^3}-1, \therefore f(3)=\mathrm{e}^3-3+a \mathrm{e}^3 < \mathrm{e}^3- \\
& 3+\mathrm{e}^3\left(\frac{3}{\mathrm{e}^3}-1\right)=0, f(4)=\mathrm{e}^4-4+a \mathrm{e}^3 \geqslant \mathrm{e}^4-4- \\
& \frac{6}{5} \mathrm{e}^3 \approx 7.39^2-4-\frac{6}{5} \times 20.09 > 0,
\end{aligned}
$$
$\therefore f(x)$ 存在唯一的零点 $x_0$, 且 $3 < x_0 < 4$.
(2) 当 $0 \leqslant x \leqslant x_0$ 时, $g(x)=x+a-\frac{x-a}{\mathrm{e}^x}$, $g^{\prime}(x)=1-\frac{1-x+a}{\mathrm{e}^x}=\frac{\mathrm{e}^x-1+x-a}{\mathrm{e}^x}, \because x > 0$, $a < 0, \therefore \mathrm{e}^x-1 > 0, x-a > 0, \therefore g^{\prime}(x) > 0$,
$\therefore g(x)$ 在 $\left(0, x_0\right)$ 单调递增, $\because 3 < x_0 < 4$,
$$
\begin{aligned}
& \therefore g\left(x_0\right) > g(3)=3+a-\frac{3-a}{\mathrm{e}^3} \geqslant 3-\frac{6}{5}-\frac{3+\frac{6}{5}}{\mathrm{e}^3} \\
& =\frac{9 \mathrm{e}^3-21}{5 \mathrm{e}^3} \approx \frac{9 \times 20.09-21}{5 \times 20.09} > 0,
\end{aligned}
$$

$$
\begin{aligned}
& \text { 又 } \because g(1)=1+a-\frac{1-a}{\mathrm{e}}=1-\frac{1}{\mathrm{e}}+a\left(1+\frac{1}{\mathrm{e}}\right) < \\
& 1-\frac{1}{\mathrm{e}}+\left(\frac{3}{\mathrm{e}^3}-1\right)\left(1+\frac{1}{\mathrm{e}}\right)=\frac{3+3 \mathrm{e}^{-}-2 \mathrm{e}^3}{\mathrm{e}^4} \approx \\
& \frac{3+3 \times 2.72-2 \times 20.09}{\mathrm{e}^4} < 0,
\end{aligned}
$$
$\therefore g(x)$ 在 $\left[1, x_0\right]$ 有唯一的零点, (注: 取 $g(0) < $

0 也可以;
当 $x > x_0$ 时, $g^{\prime}(x)=-\ln x+\frac{1}{x}-1-a < -\ln x_0$ $+\frac{1}{x_0}-1-a < -\ln 3+\frac{1}{3}-1+\frac{6}{5}=\frac{8}{15}-\ln 3 \approx$ $\frac{8}{15}-1.1 < 0$,
$\therefore g(x)$ 在 $\left(x_0,+\infty\right)$ 单调递减,
$\therefore g(4)=-3 \ln 4-5 a > -3 \ln 4-5\left(\frac{3}{\mathrm{e}^3}-1\right)=5$ $-3 \ln 4-\frac{15}{\mathrm{e}^3} \approx 0.11 > 0$, $g\left(\mathrm{e}^2\right)=2\left(1-\mathrm{e}^2\right)-a\left(\mathrm{e}^2+1\right) \leqslant 2\left(1-\mathrm{e}^2\right)+$ $\frac{6}{5}\left(\mathrm{e}^2+1\right)=\frac{16-4 \mathrm{e}^2}{5} \approx \frac{16-4 \times 7.39}{5} < 0$,
$\therefore g(x)$ 在 $\left(x_0,+\infty\right)$ 有唯一的零点,
综上, 函数 $g(x)$ 有两个零点.
6 分
(2) 由 (1) 可知 $g\left(x_1\right)=g\left(x_2\right)=0$, 其中 $1 < x_1 < $ $x_0 < x_2$, 由 $g\left(x_1\right)=0$ 得 $x_1+a-\frac{x_1-a}{\mathrm{e}^{x_1}}=0$, 即 $x_1-a\left(\mathrm{e}^{x_1}+1\right)-x_1 \mathrm{e}^{x_1}=0$, 由 $g\left(x_2\right)=0$ 得 $\ln x_2$

$$
-a\left(x_2+1\right)-x_2 \ln x_2=0,
$$
设 $h(x)=\ln x-a(x+1)-x \ln x$, 则 $h\left(x_2\right)$ $=h\left(\mathrm{e}^{x_1}\right)=0$,
$\because 1 < x_1 < x_0 < x_2, \therefore \mathrm{e}^{x_1} > \mathrm{e}, x_2 > x_0 > \mathrm{e}$,
而 $x > \mathrm{e}$ 时, $h^{\prime}(x)=\frac{1}{x}-a-\ln x-1 < \frac{1}{\mathrm{e}}-a-2$ $\leqslant \frac{1}{\mathrm{e}}+\frac{6}{5}-2=\frac{1}{\mathrm{e}}-\frac{4}{5} < 0$,
$\therefore h(x)$ 在 $(\mathrm{e},+\infty)$ 单调递减, $\therefore x_2=\mathrm{e}^{x_1}$,
要证 $\frac{\mathrm{e}^{x_2}-x_2}{\mathrm{e}^{x_1}-x_1} > \mathrm{e}^{\frac{x_1+x_2}{2}}$, 即证 $\frac{\mathrm{e}^{x_2}-\mathrm{e}^{x_1}}{x_2-x_1} > \mathrm{e}^{\frac{x_1+x_2}{2}}$, 即 $x_1$, 设 $\frac{x_2-x_1}{2}=t$, 则即证 $\mathrm{e}^t-\mathrm{e}^{-t} > 2 t$,
设 $h(t)=\mathrm{e}^t-\mathrm{e}^{-t}-2 t, t > 0$, 则 $h^{\prime}(t)=\mathrm{e}^t+\mathrm{e}^{-t}-$ $2 > 2-2=0$,
$\therefore$ 当 $t > 0$ 时, $h(t)$ 单调递增,
$\therefore h(t) > h(0)=0$, 即证.


系统推荐